Hubungan Keberadaan Tempat Penampung Air Dan Kejadian Demam Berdarah Dengue Di Puskesmas Nusajaya Kabupaten Halmahera Timur - nurlatu, nofita (Journal Of Community & Emergency, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the bite of the Aedes Aegypti mosquito which is commonly found in tropical and subtropical climates throughout the world. This disease can occur throughout the year and affects every individual regardless of age. Nusajaya Community Health Center is a DHF endemic area with a total of 40 people with DHF. One of the causes of the spread of dengue fever is the presence of water reservoirs around people’s homes that have the potential to become a breeding ground for the Aedes aegypti mosquito. The purpose of this study was to determine the relationship between the existence of water reservoirs and the incidence of dengue hemorrhagic fever at the Nusajaya Health Center, East Halmahera Regency. This type of research is analytical using a cross sectional research design, and the type of total sampling is where the number of samples is the same as the total population, namely the number of sampling is 40 people. The time in February 2022 and the research location in Nusajaya, East Halmahera Regency. The statistical test used was chi square with a 95% confidence level if < 0.05. The results of this study are the presence of water reservoirs that use a lot of 30 buckets (75.0%) and also the lack of cleanliness of the water reservoirs so that it has the potential to breed mosquitoes so that there are 40 respondents who have the incidence of dengue fever at the Nusajaya Health Center, East Halmahera Regency. The conclusion of this study is that there is a relationship between the existence of a water reservoir and the incidence of dengue hemorrhagic fever at the Nusajaya Health Center, East Halmahera Regency with a Sign value of 0.01. Suggestions in this study are expected to be input for the Puskesmas which is expected to increase the socialization of dengue prevention to the community and carry out periodic environmental control.